Business environmental policies - Vianna, Marcelo Drugg Barreto (1992)
Brazil has been through great changes, as from the second half of the current century, due to its demographic growth and to the modernization of its bases of development: from an agricultural economy predominantly turned to the export trade, the country passed to an economic activity of considerable degree of industrialization. Such phenomena resulted in significant impacts on the environment, transforming the industrial activity into a determinant, as regards the changes the country has suffered. The Brazilian participation in the World Conference on Environment, held in 1972, has led the government to feel the need of an institutional federal authority, oriented to the country's environmental preservation, being consequently created, in October 30, 1973, the Sema - Secretaria Especial do Meio Ambiente (Special Secretary for the Environment). From 1975 onwards, we can notice the establishment of agencies concerned with environmental problems in many of the member-States, as well as the appearance of specific legislation and regulatory measures for environmental control, at federal, state and local levels. In parallel, the industrial sector starts equipping itself to adjust its activities to this new set of responsibilities, reducing the emission of effluents and improving the environmental quality in industrial areas and in the metropolis. There is emergence of a concern with the environmental management, that starts its modem concepts in the planning of specific technologies to be used in industry, and also in the careful localization of facilities destined to industrial activities. In this study are presented examples of the action of some industrial sectors as concerns environmental preservation and control in Brazil. The problem of a closer relationship between the private sector and environmental organizations is a topic for discussion, with a view at enforcing projects and programs of conservation of natural resources, in pursuit of a sustainable development. As to the relationship established by the private sector with the government and society in general, should be pointed ou! the experiences effected in the region of Cubatão, in the State of São Paulo (annex 1) and the paper and cellulose plant Riocell, in Rio Grande do Sul (annex 2).